Arts leadership creating sustainable arts organizations - Foster, Kenneth J. (Mastering management in the creative and cultural industries, 2018)
The contemporary world faces unprecedented upheaval and change forcing institutions of all types to rethink how they are designed and how they must now function if they are to survive into an uncertain future. The performing arts are no exception; in an era of constant change and technological transformation, arts organizations and their leaders face significant organizational challenges if they are to maintain their relevance. Arts Leadership: Creating Sustainable Arts Organizations provides a contemporary overview of the field of arts leadership, focused on the performing arts. It examines what these challenges are, how they are affecting the performing arts and arts organizations in general and proposes creative ways to reimagine, build and lead sustainable arts organizations in this uncharted environment. With a global perspective drawn from his extensive experience advising arts organizations around the world and based on his own work successfully leading important performing arts organizations in the United States, Foster proposes an innovative approach to organizational design, systems, and structures for arts leaders in the 21st century that is based in ecological thinking and the creative process that is intrinsic to the arts. In disrupting conventional arts leadership practice, the book provides an exceptional tool to understand a unique sector, and is essential reading for students and practitioners across the creative and cultural industries